Recent advances in computational mechanics : proceedings of the 20th International Conference on Computer Methods in Mechanics (CMM2013), Poznań, Poland, 27-31 August 2013 /: proceedings of the 20th International Conference on Computer Methods in Mechanics (CMM2013), Poznań, Poland, 27-31 August 2013. ([2014]) - Unknown
No abstract available